The improvement of students’ stress resistance with the help of the development of self-regulation during university studies - Leonidovna Sokolova, Natalia (2021)
The article is devoted to the urgent problem of the formation of stress resistance in university students with the help of self-regulation training. The study highlights the specifics of examination of this phenomenon in modern science, the structure of stress resistance, and the significance and characteristics of the development of students’ stress resistance. The article also emphasizes the fact that the development of the given asset is especially effective within the self-regulation training, which is an effective method for improving the emotional-volitional component of students’ personality. The article indicates that the developed self-regulation of students and, in particular, personal self-regulation are important for the development of stress resistance. The research is aimed at studying the specifics of university students’ stress resistance with the help of self-regulation training. To achieve the goal of the research, the experiment aimed at studying the state and dynamics of students’ stress resistance was developed and carried out. The research methodology and its algorithm were selected, which included a complex psychological and pedagogical experiment and tracking the state and dynamics of stress resistance before and after the formative influence. The study was carried out at the Department of Social Pedagogy of the Institute of Foreign Languages, Peoples’ Friendship University of Russia. The study involved 56 students, the sample is representative in terms of gender and other characteristics. The results of the study allow the authors to conclude that self-regulation training is an effective method for the formation of stress resistance in students.